(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Public investments in early childhood care and education provisions (henceforth also referred to as childcare or daycare) have increased significantly in recent decades, in both developed and developing countries. Such quantitative extensions take, for example, the form of lowering compulsory schooling ages, introducing rights to a place in daycare for children at earlier ages and broadening the coverage of provisions to wider groups of children. The extension of non-parental childcare supply follows a massive growth in demand for those services. Three major trends are promoting demand for childcare services. Firstly, female emancipation in the labour market has increased maternal employment, resulting in an increased need for non-parental childcare. Secondly, while having seen considerable GDP growth since World War II, many countries still report high or even increasing child poverty rates, whereas inequalities in child outcomes emerge already in the early years. Children with single parents and without income earners in their household are especially exposed to the risk of growing up and being trapped in disadvantageous environments, requiring public investments to guarantee equality of opportunity. And thirdly, economic progress has been accompanied by significant demographic changes, reducing the number of children born. The resulting imbalance in the age structure, paired with the need for a well-trained workforce for the future’s knowledge-intensive economies, urges governments to make investments that assure that no child falls behind.